Examining Financial Behavior and Decision-Making: A Bibliometric Study of Trends and Insights - Salwa Aulia Novitasari (West Science Accounting and Finance, 2023)
This research paper presents a comprehensive bibliometric analysis of trends and insights related to behavioral finance and decision making. Utilizing bibliometric methods and VOSviewer software, this research examines publication trends, key themes, influential authors and institutions, research methodologies, and emerging trends in the field. The findings highlight the growing interest in behavioral finance and decision-making research, with publications increasing over time. Key themes include behavioral biases and heuristics, risk perception and decision making, financial literacy and education, socio-economic factors, and the impact of technology. Influential authors and institutions are identified, and various research methodologies, such as quantitative, qualitative, and mixed methods, are observed. Emerging trends include the application of machine learning, consideration of environmental and social factors, and behavioral interventions using digital platforms. Insights from this bibliometric study contribute to the understanding of the current state of knowledge in behavioral finance and decision-making, informing researchers, practitioners, and policymakers in their efforts to achieve better financial outcomes.